Enhanced aqueous Suzuki-Miyaura coupling allows site-specific polypeptide 18F-labeling. - Gao, Z; Gouverneur, V; Davis, B (2013)
The excesses of reagents used in protein chemistry are often incompatible with the reduced or even inverse stoichiometries used for efficient radiolabeling. Analysis and screening of aqueous Pd(0) ligand systems has revealed the importance of a guanidine core and the discovery of 1,1-dimethylguanidine as an enhanced ligand for aqueous Suzuki-Miyaura cross-coupling. This novel Pd catalyst system has now allowed the labeling of small molecules, peptides, and proteins with the fluorine-18 prosthetic [(18)F]4-fluorophenylboronic acid. These findings now enable site-specific protein (18)F-labeling under biologically compatible conditions using a metal-triggered reaction.